2016
DOI: 10.1016/j.kint.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Journal Club

Abstract: Urine output (UO) criterion may increase the sensitivity of the definition of acute kidney injury (AKI). We determined whether the empirically derived definition for oliguria(<0.5 ml/kg/h) is independently associated with adverse outcome. Data analysis included hourly recorded UO from the prospective, multicenter FINNAKI study conducted in 16 Finnish intensive care units. Confounder-adjusted association of oliguria of different severity and duration primarily with the development of AKI defined by creatinine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
2
5
1
Order By: Relevance
“…In contrast to previous studies, urinary output [ 21 , 29 ] and days in ICU [ 6 ] were not related to mortality in our population. Urinary output may be confounded by the use of diuretics and oliguria does not necessarily implicate the presence of AKI [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies, urinary output [ 21 , 29 ] and days in ICU [ 6 ] were not related to mortality in our population. Urinary output may be confounded by the use of diuretics and oliguria does not necessarily implicate the presence of AKI [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, in a comparison of the sCr criterion alone with the urine output criterion alone for the diagnosis of AKI in patients after cardiac surgery, Lagny et al indicated that the use of the urine output criterion alone could lead to overdiagnosis [ 32 ]. In a recent multicenter prospective study that assessed the association between the hourly urine output and mortality, Vaara et al reported that patients who fulfilled both the sCr and urine output criteria had the highest rate of RRT initiation and the highest 90-day mortality, while isolated oliguria was associated with poor outcomes; these results affirm the importance of measuring the hourly urine output and the need to combine the urine output criterion with the sCr criterion [ 33 ]. Moreover, in using the urine output criterion in the diagnosis and staging of AKI, there is a concern that the use of diuretics may change the urine output, causing underestimation of the AKI severity.…”
Section: Commentarymentioning
confidence: 99%
“…Data on the prognostic value of clinical examination findings are inconsistent. Previous studies have identified different predictors of mortality such as low blood pressure (6, 9, 10), oliguria (3, 5), prolonged capillary refill time (CRT) (11, 12), and skin mottling (4, 13). They often evaluated one or two clinical signs in isolation, instead of assessing a combination of signs and symptoms, which would more accurately reflect daily clinical practice.…”
mentioning
confidence: 99%